2020
DOI: 10.1109/tie.2019.2945264
|View full text |Cite
|
Sign up to set email alerts
|

An Approach Towards Extreme Fast Charging Station Power Delivery for Electric Vehicles with Partial Power Processing

Abstract: This article proposes an approach for realizing the power delivery scheme for an extreme fast charging (XFC) station that is meant to simultaneously charge multiple electric vehicles (EVs). A cascaded H-bridge converter is utilized to directly interface with the medium voltage grid while dual-active-bridge based soft-switched solid-state transformers are used to achieve galvanic isolation. The proposed approach eliminates redundant power conversion by making use of partial power rated dc-dc converters to charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(81 citation statements)
references
References 28 publications
1
79
0
1
Order By: Relevance
“…Power electronics are a fundamental part of the fast-charging station. The right choice of the power converters' topologies and the selection of the power semiconductors are the key factors in improving the efficiency and the power density of the charging units [12,13]. In [14] the electric bus was equipped with a pantograph in order to test the Flash Charge (at the bus stop), as illustrated in Figure 1.…”
Section: State Of the Artmentioning
confidence: 99%
“…Power electronics are a fundamental part of the fast-charging station. The right choice of the power converters' topologies and the selection of the power semiconductors are the key factors in improving the efficiency and the power density of the charging units [12,13]. In [14] the electric bus was equipped with a pantograph in order to test the Flash Charge (at the bus stop), as illustrated in Figure 1.…”
Section: State Of the Artmentioning
confidence: 99%
“…Indeed, comparing [48] and [49], it is concluded that applying a multi-input DAB converter achieves higher efficiencies. Then, there is the auxiliary architecture proposed in [44]. However, authors conclude that the obtained converter is slightly less efficient (-0.3%) and bigger (+10%).…”
Section: ) Overviewmentioning
confidence: 99%
“…Then, due to its simplicity, phase shift modulation (PSM) is chosen for controlling the power flow between the source and the load. On the other hand, in order to observe the benefits of PPC architectures and based on [26], [44], the circuit shown in Figure 13 is compared to its FPC version, see Figure 14. Finally, Table 7 details the circuit parameters from Figure 13 and Figure 14.…”
Section: A Architecture and Topology Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19] present PPP architectures for applications where there exist series connected elements. Last but not least, when it comes to EV fast charging applications authors from [8,20,21] propose PPP based charging units. There, the authors implement a unidirectional topology such as the phase shifted full bridge and they show that the PPP solution achieves converter rating reduction and efficiency improvements compared to its full power processing (FPP) version.…”
Section: Introductionmentioning
confidence: 99%